Higher Adalimumab Drug Levels During Maintenance Therapy for Crohn's Disease Are Associated With Biologic Remission. Issue 6 (17th October 2018) - Plevris, Nikolas; Lyons, Mathew; Jenkinson, Philip W; Chuah, Cher S; Merchant, Lynne M; Pattenden, Rebecca J; Watson, Eleanor F; Ho, Gwo-Tzer; Noble, Colin L; Shand, Alan G; Din, Shahida; Arnott, Ian D; et al.
Abstract: Background: Adalimumab is an established treatment for Crohn's disease. Limited data are available regarding the relationship between adalimumab drug levels and serum/fecal markers of gut inflammation. We therefore aimed to characterize the relationship between adalimumab levels and biologic remission during maintenance therapy. Methods: A single-center prospective cross-sectional study was undertaken on Crohn's disease patients who had received adalimumab therapy for a minimum of 12 weeks after induction. Data on clinical activity (Harvey-Bradshaw Index), C-reactive protein (CRP), adalimumab drug and antibody levels, and fecal calprotectin were collected. Biologic remission was defined as a CRP <5 mg/L and fecal calprotectin <250 µg/g. Adalimumab drug and antibody levels were processed using the Immundiagnostik monitor enzyme-linked immunosorbent assay. Results: One hundred fifty-two patients had drug and antibody samples matched with CRP and fecal calprotectin. Patients in biologic remission had significantly higher adalimumab levels compared with others (12.0 µg/mL vs 8.0 µg/mL, P < 0.0001). Receiver operating characteristic curve analysis demonstrated an optimal adalimumab level of >8.5 µg/mL (sensitivity, 82.2%; specificity, 55.7%; likelihood ratio, 1.9) for predicting biologic remission. Multivariable logistic regression revealed that adalimumab levels >8.5 µg/mL were independently associated with biologic remission (odds ratio, 5.27; 95% confidence interval, 2.43–11.44; P < 0.0001). Conclusions: Higher adalimumab levels are associated with biologic remission. An optimal level of >8.5 µg/mL was identified.